The Effects of Behavioral Contracting Technique for Reducing Disruptive Behaviors of Students: A Single Subject Study - Intan Sari, Siwi Vilia; Sugiharto, DYP; Mulawarman, Mulawarman (Jurnal Bimbingan Konseling, 2022)
Disruptive behaviors during class can interfere with teaching and learning activities. Behavioral contracting is one of the techniques in the behavioral approach that was chosen to use in assisting students to achieve full awareness to surge self-control. This study aimed to examine the effectiveness of behavioral contracting techniques to reduce disruptive behaviors of students at SMK Muhammadiyah Kajen Pekalongan. The subjects included 2 students selected by the purposive random sampling method. The data collection instrument consisted of an observation sheet with a frequency-measuring form. The design of this study was a single-subject design (SSD) in a pattern of A - B - A. Visual analysis of the graph intended to find the average score, level, trend, stability, and data overlap. The results of this analysis indicate a change in level and trend from stable to a decrease in the frequency of disruptive behavior which can then be concluded that the behavior contract technique is effective for reducing disruptive behavior in students. Further research is recommended to join other techniques with behavioral contracting.